Menguatkan Motivasi Belajar: Peran Orang Tua selama Pandemi Covid-19 pada Siswa Sekolah Dasar - Larasati, Destia; Wafiqni, Nafia (Elementar : Jurnal Pendidikan Dasar, 2023)
The purpose of this study was to know the relationship between the role of parents and the learning motivation of fourth grade students at SDN Semanan 08. This study uses a quantitative method with a correlation design. This research was conducted at SDN Semanan 08 with a sample of 32 students. Data collection technique was carried out using a questionnaire instrument on the role of parents and learning motivation with a Likert scale model. The data analysis techniques used in this research are validity test, reliability test, descriptive statistical test, normality test, linearity test and hypothesis testing. The results of this study indicate that there is a significant relationship between the role of parents and students' learning motivation with a calculated r value of 0.830 > 0.349 (r table), then H0 is rejected, H1 is accepted. It can be concluded that the role of parents is very influential in the learning motivation of fourth grade students at SDN Semanan 08.